AQP4-specific T cells determine lesion localization in the CNS in a model of NMOSD - Ali Maisam Afzali; Oleksii Ulianov; Luise Eckardt; Ingrid Stas; Lea Seeholzer; Katja Steiger; Doron Merkler; Thomas Korn (Acta Neuropathologica Communications)
Abstract Neuromyelitis optica spectrum disorder (NMOSD) is a paradigmatic autoimmune disease of the central nervous system (CNS), in which the water channel protein Aquaporin-4 (AQP4) is targeted by a self-reactive immune response. While the immunopathology of human NMOSD is largely dependent on antibodies to astrocytic AQP4, the role of AQP4-specific T cells for the localization and quality of NMOSD lesions in the CNS is not known. Only recently, we established that thymic B cells express and present AQP4 in the context of MHC class II molecules to purge the naive T cell receptor repertoire of AQP4-specific clones. Here, we exploited this finding to investigate the lesion localization in the CNS of B cell conditional AQP4-deficient (Aqp4 ΔB) mice, which harbor AQP4-specific precursors in their naive T cell repertoire and can be sensitized to mount a strong AQP4(201–220)-specific CD4+ T cell response. Sensitization of Aqp4 ΔB mice with AQP4(201–220) was sufficient to induce clinical disease. The spatiotemporal lesion distribution and the glial cell response in AQP4(201–220)-induced experimental autoimmune encephalomyelitis (EAE) was compared to classical MOG(35–55)-induced EAE in Aqp4 ΔB mice. In contrast to MOG-EAE, AQP4(201–220)-induced EAE was characterized by midline lesions in the brain, retinal pathology, and lesions at the grey matter/white matter border zone in the spinal cord. Therefore, we conclude that antigen-specific T cells dictate the localization of NMOSD-lesions in the CNS.